Measurement Invariance pada Indonesian Tawadhu Scale (ITS) - Yonathan Natanael; Mirna Devi; Yasril Ananta Burhanudin; Jamiludin Nur (Jurnal Psikologi Islam dan Budaya, 2020)
The purpose of this study to develop a new instrument of tawadhu that valid, unbiased, and can be used in Indonesia. The research method uses combination similarization in Islamic Psychological studies and psychological construction scale. The number of participants in this research is 613 Muslims with range 16 to 45 years old. Instrument consists of 7 items measuring intrapersonal dimension and 13 items measuring interpersonal dimension. Methods that used measuring instrument testing are Aiken validity and Multiple Groups Confirmatory Factor Analysis (MGCFA) with a multidimensional model. The results of Aiken analysis show that all items are valid measuring tawadhu. Also, MGCFA shows that Indonesian Tawadhu Scale is an unbias scale. This instrument can be used by Muslims in Indonesia as it integrates the concept of Psychology and Islam.